Synthesis, structural characterization and properties evaluation of two new zwitterionic siloxane compounds. (15th March 2020) - Bargan, Alexandra; Cazacu, Maria; Dascalu, Mihaela; Macsim, Ana-Maria; Soroceanu, Alina; Macsim, Ioan Florin
Graphical abstract: Highlights: Single-crystals synthesis of 1, 3-bis(3-ammoniumpropyl)tetramethyldisiloxane salts. The new compounds were characterized by different specific methods. The thermal and moisture stability for these new compounds were studied. The crystalline salts can be used as capture media-host for multiple guest gases. Abstract: 1, 3-Bis(3-aminopropyl)tetramethyldisiloxane is a valuable tool for the introduction of siloxane segments into different organic-inorganic structures. This paper demonstrates how 1, 3-bis(3-aminopropyl)tetramethyldisiloxane can easily form crystalline salts with different counterparts with which it comes into contact. Thus, in the reaction chamber 1, 3-bis(3-ammoniumpropyl)tetramethyldisiloxane chloride and nitrate were formed in the detriment of one stage metal (Ni and Cu) complexes of Schiff's base with 4-imidazole carboxaldehyde. The salt products were isolated in crystalline state and were structurally characterized by single-crystal X-ray diffraction, elemental and spectral (FT-IR, 1 H NMR) analysis. The thermal and moisture stability as well as the aggregation ability in solution and sorption capacity for certain molecules were evaluated by adequate techniques.